Glucose sensing and light regulation: A mutation in the glucose sensor RCO-3 modifies photoadaptation in Neurospora crassa. Issue 6 (June 2018) - Olmedo, María; Roenneberg, Till; Merrow, Martha; Corrochano, Luis M.
Abstract: Light regulates fungal gene transcription transiently leading to photoadaptation. In the ascomycete Neurospora crassa photoadaptation is mediated by interactions between a light-regulated transcription factor complex, the white collar complex, and the small photoreceptor VVD. Other proteins, like the RCO-1/RCM-1 repressor complex participate indirectly in photoadaptation. We show that RCO-3, a protein with high similarity to glucose transporters, is needed for photoadaptation. The mutation in rco-3 modifies the transcriptional response to light of several genes and leads to changes in photoadaptation without significantly changing the amount and regulation of WC-1. The mutation in rco-3, however, does not modify the capacity of the circadian clock to be reset by light. Our results add support to the proposal that there is a connection between glucose sensing and light regulation in Neurospora and that the fungus integrates different environmental signals to regulate transcription.